(untitled) (Carte Romanze, 2021)
Besides the author of Branch 3 of the Roman de Renart draws extensively from the oral narrative patrimony for the writing of his tale, nevertheless the episode of the wolf taking monastic vows comes from a quite different tradition, which is literary and religious. Far from being incidental, we try to argue that the entire articulation of the Branch depends just on such insertion, both as regards the choice of the folkloric material (that is the two tales of the “theft of the fish from the cart” and the “fishing with the tail”), and its reinterpretation in a Renardian guise.